Effect of metformin on adverse outcomes in T2DM patients: Systemic review and meta-analysis of observational studies - Xu, Zhicheng; Zhang, Haidong; Wu, Chenghui; Zheng, Yuxiang; Jiang, Jingzhou (Frontiers in Cardiovascular Medicine, 2022)
Background: The cardiovascular protection effect of metformin on patients with type 2 diabetes mellitus(T2DM) remains inconclusive. This systemic review and meta-analysis were to estimate the effect of metformin on mortality and cardiovascular events among patients with T2DM. Methods: A search of the Pubmed and EMBASE databases up to December 2021 was performed. Adjusted hazard ratios(HRs) and 95% confidence intervals (CIs) were pooled by a random-effects model with an inverse variance method. Results: A total of 39 studies involving 2473009 T2DM patients were adopted. Compared to non-metformin therapy, the use of metformin was not significantly associated with a reduced risk of major adverse cardiovascular event(MACE)(HR=1.06, 95%CI 0.91-1.22; I²=82%), hospitalization(HR=0.85, 95%CI 0.64-1.13; I²=98%), heart failure(HR=0.86, 95%CI 0.60-1.25; I²=99%), stroke(HR=1.16, 95%CI 0.88-1.53; I²=84%), and risk of AMI(HR=0.88, 95%CI 0.69-1.14; I²=88%) in T2DM patients. Metformin was also not associated with significantly lowered risk of MACE compared to dipeptidyl peptidase-4 inhibitor(DPP-4i) in T2DM patients(HR=0.95, 95%CI 0.73-1.23; I2=84%). Conclusions: The effect of metformin on some cardiovascular outcomes was not significantly better than the non-metformin therapy or DPP-4i in T2DM patients based on observational studies.